Determination of beams’s parameters with lumped mass by using measurement data of vibrations - Menh, Nguyen Cao; Toan, Tran Trong (Vietnam Journal of Mechanics, 1996)
In this paper the transverse vibration of the clamped-free beam with lumped mass is investigated. From that the inverse problem for determining the length of the beam on the basis of measurement data of beam’s vibration with changing mass is solved by numerical method. The computer programs for the problem are to be applied to some examples and the obtained results are acceptable. The common solution for problems with different lumped masses is chosen as desirable result.